Living Islamic Work Ethics: A Phenomenological Study of Teacher Meaning-Making in Islamic Integrated Schools - Zaroni, Akhmad Nur; Norvadewi, Norvadewi; Muhaimin, Muhaimin; Darmawati, Darmawati; Syata, Samsir (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
The goal of the research is to find out the comprehension, internalization, and the practical side of the Islamic Work Ethics (IWE) concept by the teaching staff of an Integrated Islamic Junior High School (SMPIT) located in East Kalimantan. The study applies the interpretive phenomenological analysis (IPA) technique to highlight the teachers’ experiences in the course of balancing the spiritual values, the demands of the organization, and the social responsibilities. The research used semi-structured interviews, observations, and school documents to collect data, and then the data was analysed by the method of iteration to find out the main themes. The results uncovered four overarching themes that can be summarized as follows: (1) work as a form of worship and a responsibility that nurtures inner drive and ethical devotion; (2) the principal's (uswah hasanah) exemplary leadership is the major factor that either fortifies or undermines the practice of IWE; (3) the continuing interaction between the ideal religious principles and the organizational structures, especially in relation to work, administration, and pay issues; and (4) the promotion of IWE as a social distinction that places teachers in the role of moral protectors of the community. The research findings indicate that IWE is more than just a personal moral quality, rather, it is a lively and dynamic interpretable framework directed by the expected spirituality, the organizational environment, and the cultural norms. By this research, the theoretical engagement with IWE moves toward a phenomenological understanding and contributes to the discussions on the practical and policy implications of work culture strengthening, ethical leadership, and teacher well-being in Islamic educational institutions.